Native Customary Land Rights In Sabah - Wong-Adamal, Juprin (Journal of Malaysian and Comparative Law, 2019)
Native customary land rights in Sabah are in integral part of the land laws as provided for under the Land Ordinance (hereinafter referred to as "the Ordinance") which is a principal source of substantive land laws in Sabah. This paper look into the ingredients of native customary land rights and the importance placed on them that reflect the ways of life of the indigenous peoples of Sabah or as they are aptly and legally referred to, the native of Sabah.